Industry expectations for beginning agricultural lenders. Issue 4 (24th April 2020) - Hanson, Erik; Wachenheim, Cheryl Joy
Abstract : Purpose: This paper aims to describe the nature of an agricultural lending position and reports an industry perspective of skills required for a new graduate entering the profession. Design/methodology/approach: Loan officers and those directly supervising loan officers were surveyed regarding job characteristics and perceptions of the skills needed for career success. Findings: Lenders perceive on-the-job training to be slightly more valuable than post-secondary training for preparing students for a career in agricultural lending. Financial skills were rated to be roughly as important as non-financial skills for early career success. Financial topics identified as important include financial statements, breakeven analysis and accrual-basis earnings. Communication and risk analysis were rated as the most important non-financial topics needed for early career success. Regarding their jobs, lenders indicated that they devote much of their time to managing loans and developing or maintaining relationships with customers. Benefits were identified as the most important feature for job satisfaction, particularly among agricultural lenders, that also work essentially full time on a farm or ranch. Work environment, work flexibility, location and salary were also considered to be important job characteristics. Originality/value: This paper updates the literature regarding industry's preferred skills and refines the surveyed audience to only those currently performing or directly supervising agricultural lending. It adds a unique perspective on the work time allocated to various agricultural lending activities and lenders' valuation of job characteristics. These insights may guide curricular and course design, career planning and employee recruitment and marketing efforts.